2014
DOI: 10.1161/circgenetics.111.000007
|View full text |Cite
|
Sign up to set email alerts
|

FTO Genotype, Physical Activity, and Coronary Heart Disease Risk in Swedish Men and Women

Abstract: Background-Variants in the fat mass-and obesity-associated gene (FTO) predisposing to obesity and diabetes mellitus have also been associated with cardiovascular disease. Physical activity has been suggested to attenuate the FTO effect on obesity, but it is unknown whether this is also true for cardiovascular disease. Therefore, we explored whether physical activity modifies the FTO association with coronary heart disease (CHD). Methods and Results-FTO rs9939609 (T>A) polymorphism was genotyped in 2 Swedish po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Zavatarri et al51 showed no association between the FTO rs9939609 polymorphism and the parameters of lipid metabolism and stressed that AA homozygotes are particularly predisposed to obesity. Population studies conducted by Gustavsson et al52 on Gothenburg residents confirmed that AA and TA genotypes have a greater WC and a higher BMI compared to TT genotype.…”
Section: Discussionmentioning
confidence: 92%
“…Zavatarri et al51 showed no association between the FTO rs9939609 polymorphism and the parameters of lipid metabolism and stressed that AA homozygotes are particularly predisposed to obesity. Population studies conducted by Gustavsson et al52 on Gothenburg residents confirmed that AA and TA genotypes have a greater WC and a higher BMI compared to TT genotype.…”
Section: Discussionmentioning
confidence: 92%
“…Gustavsson et al . found that the minor allele of the FTO gene was associated with higher proportion of subjects with overweight and obesity. They also reported that there was no association of FTO genotypes with blood lipids and physical activity levels.…”
Section: Discussionmentioning
confidence: 95%
“…This SNP is known to predispose to obesity, type II diabetes and cardiovascular diseases and has also been linked to psychological disorders. [55][56][57][58] A longitudinal study in Brazil found a 0.07 kg/m 2 /year weight gain for each additional risk allele. 59 It has been previously reported that the overall risk of obesity is increased~1.3-fold per risk allele.…”
Section: Discussionmentioning
confidence: 99%